INCREASING VOCABULARY MASTERY OF VIII GRADE STUDENTS AT SMP NEGERI 4 TOLITOLI THROUGH PICTURE - Ismail Yunus H (Jurnal Madako Education, 2017)
This research Includes an experimental research which consists of four stages; Planning, action, observation and relection. The subjects of this study are students of class VIII E SMP Negeri 4 Tolitoli academic year 2016 / 2017.This research used 17 students as a sample from score this study can be seen from the average value of each value pre test and post test. Where the score pretest in this study.  The result of the test showed that the students’ mean score in post test 84.88 is high than pretest 51.25. The researcher found  that  the  T-table  is  2,131  was  identified  at  15  the  significance level is 0,05 and T counted  Is 14,977, it   meant  that  the   Tcounted   was  higher   than   Ttable   and   the  hypothesis  is  accepted. The  researcher concluded that  using  picture  can increase  vocabulary  mastery  of  VIII  Grade  students  at  SMP Negeri 4 Tolitoli through Picture. Based on these results, the researcher draw the conclusion that the media pictures can improve the mastery of  vocabulary in the students of class VIII E SMP  Negeri  4  Tolitoli academic year  2016 / 2017. From facts, the authors suggest English teachers to be more creative which to make students more active and enjoy in learning English. The researcher also suggest to students to emphasize themselves for more enterprising learning more actively ask questions and to seek more knowledge.     Keywords: Increasing Students Vocabulary Mastery, using Pictures.